2008
DOI: 10.1080/10826080802108293
|View full text |Cite
|
Sign up to set email alerts
|

Not All Injection Drug Users Are Created Equal: Heterogeneity of HIV, Hepatitis C Virus, and Hepatitis B Virus Infection in Georgia

Abstract: Injection drug users (IDU) are widely believed to have accelerated the looming HIV/AIDS epidemic now faced by the Russian Federation and countries of the former Soviet Union. However, IDUs may be heterogeneous with regard to risk behaviors and a sub-population may be responsible for the majority of blood-borne pathogen transmission. We studied 926 adult injection drug users (IDU) from the cities of Tbilisi, Batumi, and Poti in Georgia, a small country in the Caucuses region between the Black and Caspian Seas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In Estonia and Lithuania, an estimated 58–70% of PWID had been in prison at least once 74. In Georgia and Russia, this figure was between 6% and 37%,18 52 64 65 79 121 122 In Central Europe, between 18% and 50% of respondents report previously having been in prison 93 107…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Estonia and Lithuania, an estimated 58–70% of PWID had been in prison at least once 74. In Georgia and Russia, this figure was between 6% and 37%,18 52 64 65 79 121 122 In Central Europe, between 18% and 50% of respondents report previously having been in prison 93 107…”
Section: Resultsmentioning
confidence: 99%
“…Estimates of HIV prevalence among PWID vary widely throughout the region. A total of 79 sources reported HIV prevalence estimates (some multiple), of which 67 reported unique HIV prevalence estimates among PWID in the region; 44 from Eastern Europe and Central Asia 6 49–88 and 21 from Central Europe 89–109 and two that contained data from both regions. 40 110 …”
Section: Resultsmentioning
confidence: 99%
“…In particular, men ages 40–49 years had the highest prevalence of both reported IDU (17.4%, data not shown) and anti-HCV (22.7%). (This cohort came of age during a drug trafficking and IDU epidemic in Georgia during the 1990s/early 2000s following the collapse of the former Soviet Union [23]). However, injecting behavior poses an important challenge for HCV elimination regardless of the age of persons injecting, and those actively injecting drugs will be a key target to curb transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research reported that in some subgroups more than four out of five opioid-injecting drug-using men in Georgia are sharing needles with others [26,27]. Thus, even if the opioid-injecting male partners of illicit-drug-free females are not having sex with other women or men, the male partner remains at high risk of getting infected with HIV and HCV and passing these infections to his female partner through sexual contact.…”
Section: Discussionmentioning
confidence: 99%